1996
DOI: 10.1088/0953-4075/29/4/027
|View full text |Cite
|
Sign up to set email alerts
|

Absolute negative conductivity in Xe/Cs mixture under photoionization conditions

Abstract: The phenomenon of absolute negative conductivity in Xe/Cs mixtures under narrow-band photoionization conditions is investigated. Both the pulsed mode of photoionization of Xe/Cs mixtures and the stationary mode with additives of electronegative gases are considered. It is shown that under narrow-band ionization conditions in the pulsed mode, the absolute magnitude of negative conductivity can greatly exceed the value of negative conductivity in a dissociative plasma created by wide-band radiation. The possibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…It was shown that during the EEDF relaxation there exists a time interval where the electron mobility is negative. The TNM effect was also numerically studied in [33] (for pure Xe) and [34] (for Xe:Cs mixture), in which the initial f 0 (ε) was assumed to be a narrow Gaussian distribution around a certain energy.…”
Section: Transient Negative Mobilitymentioning
confidence: 99%
“…It was shown that during the EEDF relaxation there exists a time interval where the electron mobility is negative. The TNM effect was also numerically studied in [33] (for pure Xe) and [34] (for Xe:Cs mixture), in which the initial f 0 (ε) was assumed to be a narrow Gaussian distribution around a certain energy.…”
Section: Transient Negative Mobilitymentioning
confidence: 99%
“…The rate constants kej for pair collisions with electrons were taken from solution of Boltsman equation [7] solved together with the kinetic equations system by numerical method used and approved earlier in papers [8,9]. The solutions were found in assumptions of homogenous distribution of all plasma components.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…However, negative resistors facilitate the construction of such -ports. The theoretical works on the existence of negative conductivity in plasmas [8], [29], semiconductors [10], and solids of special microscopic structures, e.g., semiconductor superlattices [4], [15] and graphene [27], seem to herald the advent of certain circuit elements of negative conductance, let alone implementations by transistor negative-resistance converters [3] or Tunnel diodes (as early as in 1960 Youla claimed that negative resistors are on their way to becoming practical building blocks [31]). Such elements can be used to build linear -ports which allow the mentioned port states even if no independent internal generators are present ( -port equations being homogeneous).…”
Section: Introductionmentioning
confidence: 99%
“…How the excess energy delivered by an element is supplied depends on the mechanism responsible for the development of negative conductivity. It is typically supported by bias electric or magnetic fields [10], [22], photoionization (in plasmas) [29], and various pumping mechanisms like optical or microwave irradiation [12], [26]. For a microscopical theory explaining how such a system evolves from zero resistance state to absolute negative conductivity see [12], where also further references on the ongoing controversial discussion and first experimental confirmations are given.…”
Section: Introductionmentioning
confidence: 99%